2017
DOI: 10.1111/jfb.13459
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome characterization of HPG axis from Chinese sea perch Lateolabrax maculatus

Abstract: Here the transcriptome and differential gene expression in the adult brain and gonads of the Chinese sea perch Lateolabrax maculatus were reported. A total of 78 256 909 clean reads were generated from the adult brain, ovary and testis by using the Illumina HiSeq2000 platform and assembled into 274 909 contigs. A total of 31 683 unigenes were annotated based on sequence similarity and 20 702 unigenes were found to exhibit 8237 gene ontology terms and 3888 signal pathways. Transcripts of 26 623 unigenes were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, a comprehensive transcriptome analysis identified sequences of genes involved in salinity adaptation and osmoregulation in the liver of the spotted sea bass, providing insights into the molecular mechanisms behind salinity acclimation in euryhaline teleosts [4]. The profile of differential gene expression in the adult brain and gonads for the spotted sea bass laid the foundation for the understanding of hypothalamus-pituitary-gonad axis gene function and reproduction regulation in teleosts [11]. …”
Section: Data Descriptionmentioning
confidence: 99%
“…In addition, a comprehensive transcriptome analysis identified sequences of genes involved in salinity adaptation and osmoregulation in the liver of the spotted sea bass, providing insights into the molecular mechanisms behind salinity acclimation in euryhaline teleosts [4]. The profile of differential gene expression in the adult brain and gonads for the spotted sea bass laid the foundation for the understanding of hypothalamus-pituitary-gonad axis gene function and reproduction regulation in teleosts [11]. …”
Section: Data Descriptionmentioning
confidence: 99%
“…Gonadotropin-releasing hormone, synthesized and secreted by the hypothalamus, enters the pituitary through the pituitary portal system and regulates the secretion of gonadotropins, such as luteinizing hormone, follicle-stimulating hormone and prolactin, thereby promoting gonadal secretion of sex hormones, such as oestrogen and testosterone. 36 Long-term pressure inhibits this axis, and the levels of oestrogen and testosterone secreted by the gonads decrease, which may lead to the occurrence and development of oral mucosal diseases.…”
Section: Neurobiological Mechanismsmentioning
confidence: 99%
“…and testis tissues, respectively, while 26623 unigenes were commonly expressed in all HPG tissues [25]. Xu et al analyzed the gene expression of HPG axis in Cyprinus carpio and suggested that 9, 28, and 212 genes were differentially expressed in hypothalamus, pituitary, and ovary, respectively [26].…”
Section: Plos Onementioning
confidence: 99%